Do older workers suffer more workplace injuries? A systematic review - Bravo, Gonzalo (2022)
Aging populations are a dramatically increased worldwide trend, both in developed and developing countries. This study examines the prevalence of fatal and non-fatal work-related injuries between young (<45 years old) and older (>= 45 years old) workers. A systematic literature review aimed at examining studies comparing safety outcomes, namely fatal and non-fatal injuries, between older and younger workers. Results show that 50% of the reviewed papers suggest that fatal injuries are suffered mainly by older workers, while the remaining 50% show no differences between older and younger workers. Regarding non-fatal injuries, 49% of the reviewed papers found no relationship between workers' age; 31% found increased age as a protective factor against non-fatal injuries; and 19% showed that older workers had a higher risk of non-fatal injuries than younger ones. This review suggests that older workers experience higher rates of fatal injuries, and younger workers experience higher rates of non-fatal injuries.